1967
DOI: 10.1677/joe.0.0380351
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Obesity in Male Rats After Placement of Ventromedial Hypothalamic Lesions at Four Different Ages

Abstract: Ventromedial hypothalamic lesions in weanling female rats have been reported to result in a greater reduction of growth than placement of such lesions in older animals (Bernardis & Skelton, 1966). The present report deals with a parallel study in male rats of corresponding ages.Male Holtzman rats received bilateral electrolytic lesions at the age of 26 days (Group 1), 59 days (Group 3), 75 days (Group 5) and 140 days (Group 7). Nonlesioned rats of the same age served as controls (Groups 2, 4, 6 and 8). The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 4 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…Han et al (1965) and Bernardis and Skelton (1965) confirmed these findings and the latter authors observed, in addition, a decrease in the number of pituitary acidophils in spite of an intact median eminence. Similar findings were then reported for the male weanling rat (Bernardis and Skelton, 1967) and extended by the observation (Bernardis and Frohman, 1967;Frohman and Bernardis, 1968) that plasma and pituitary growth hormone (GH) levels were decreased as measured by radioimmunoassay in the weanling rat with VMN lesions. These changes were subsequently shown to correlate with the size of the lesion .…”
supporting
confidence: 79%
“…Han et al (1965) and Bernardis and Skelton (1965) confirmed these findings and the latter authors observed, in addition, a decrease in the number of pituitary acidophils in spite of an intact median eminence. Similar findings were then reported for the male weanling rat (Bernardis and Skelton, 1967) and extended by the observation (Bernardis and Frohman, 1967;Frohman and Bernardis, 1968) that plasma and pituitary growth hormone (GH) levels were decreased as measured by radioimmunoassay in the weanling rat with VMN lesions. These changes were subsequently shown to correlate with the size of the lesion .…”
supporting
confidence: 79%
“…The syndrome thus appears to have certain features in common with that resulting from bilateral destruction of the ventromedial nuclei in weanling rats (Han et al, 1965;Frohman & Bernardis, 1968;Bernardis & Skelton, 1965, 1967. Han et al (1965) and Bernardis & Skelton (1965, 1967 reported that extensive lesions in the ventromedial nuclei of weanling rats were associated with stunting and an increase in carcass fat without increased food intake. Excessive weight gain was not observed even when the rats were followed for several months.…”
Section: Discussionmentioning
confidence: 95%
“…No estimate of energy expenditure was undertaken in the present study and further detailed examination of the pattern of food intake in treated animals and of energy expenditure appear indicated. Han et al [18] and Bernardis & Skelton [19,20] have shown that weanling rats with electrolytic lesions in the ventromedial hypothalamic nuclei became obese without excessive caloric intake. Frohman and Bemardis [6] concluded that at least one major factor contributing to excessive accumulation of adipose tissue in VMN lesioned weanling rats was growth hormone deficiency resulthag from the hypothalamic lesions.…”
Section: Discussionmentioning
confidence: 99%